Comparative Analysis of Ship Lighting Systems in Terms of Economic, Environmental and Material Performance - Yigit, K.; Kokkulunk, G.; Savas, O. (POLISH ACAD SCIENCES INST PHYSICS, 2018)
The uses of energy-efficient light sources on the shipboards play a significant role in the today's maritime sector. In this paper the performance of the lighting system of the bulk carrier ship named M/V Ince Anadolu is examined. In the case study the use of light emitting diode (LED) lamps on the shipboard instead of the existing lighting system is proposed. The existing lighting and LED lighting systems of the ship are compared in terms of economic, environmental and material performance. The results show that the energy-efficient lighting system on the shipboards decreases the operating costs, the fuel consumption and the exhaust emissions compared to the traditional lighting systems. The proposed lighting system provides a higher strength of light bulbs, required in the difficult sea conditions, due to better material specifications.
Keywords: Physics